EFFECT OF QUIZLET USE ON UKRAINIAN SERVICE MEMBERS’ ENGLISH VOCABULARY ACQUISITION - N. Yu. Todorova (Novìtnâ Osvìta, 2023)
The article focused on exploring the effect of the use of Quizlet on Ukrainian service members’ English vocabulary acquisition and their perceptions of its utilisation in the educational process. A mixed-method research design combining quantitative and qualitative approaches was employed in this experimental study, which consisted of 3 stages. The data for the analysis were collected through 3 survey questionnaires and 2 tests. The obtained results reported a beneficial effect of Quizlet integration into the English language course on the service members’ English vocabulary mastery. The participants demonstrated high learning outcomes and significant English vocabulary acquisition progress after systematic and continued Quizlet utilisation in and out of class. Ukrainian service members positively responded to Quizlet implementation during the course and supported its further integration into the programme. The participants viewed Quizlet as an effective learning tool and highly valued its practical use. They praised Quizlet's simplicity, convenience, mobility, and time-saving abilities but underestimated its motivating and entertaining potential. Under the current conditions of the increased demand for English-speaking personnel, this study can contribute to the development of practice guidelines for the incorporation of Quizlet and other vocabulary-building mobile applications into the English language courses for military professionals at higher military educational institutions.